Fluocinolone Acetonide Implant as a Baseline Therapy for Diabetic Macular Edema: Results from the Randomized Phase 4 NEW DAY Study - Michael A. Singer; Charles C. Wykoff; Christopher D. Riemann; Victor H. Gonzalez; Christina Y. Weng; Kamel Alkhatib; Scott Moody; Mary Pao (Therapeutic Advances in Ophthalmology, 2026)
Summary This summary explains the findings of the NEW DAY study, which examined two ways of starting treatment for diabetic macular edema (DME). DME is an eye condition that can affect people with diabetes and can cause blurred vision or vision loss if not treated. In the 18-month study, adults with DME who had little or no previous treatment started therapy with either a single fluocinolone acetonide (FAc) implant or a series of aflibercept injections. The FAc implant is a small device placed inside the eye and is designed to slowly release a corticosteroid up to 3 years. Aflibercept is a medicine given as a series of eye injections. After the planned starting treatment, people in both groups could receive extra (“rescue”) aflibercept injections if their vision worsened or if eye scans showed worsening DME (retina swelling). After the planned starting treatments, both groups needed a similar number of rescue injections. However, counting the planned starting treatments plus the rescue injections, people who received the FAc implant had fewer total injections and went longer before needing their first rescue injection. Vision and retina swelling improved similarly between groups. Side effects such as cataracts and increases in eye pressure were more common with the FAc implant. Such side effects are expected when steroids are given in the eye and manageable with regular checkups and treatment. Overall, compared with starting DME treatment with aflibercept, starting with the FAc implant reduced the total number of injections while providing similar vision and eye scan improvements. What is this summary about? This is a plain language summary of the results of the NEW DAY study published in Ophthalmology 2026 Jul;133(7):837-851. doi: 10.1016/j.ophtha.2026.03.019. NEW DAY compared ILUVIEN ® , a fluocinolone acetonide implant ( FAc ), with aflibercept in people with diabetic macular edema ( DME ) who had minimal or no prior treatment for that condition. DME is a complication of diabetes that affects the eye, causing blurred vision and potential vision loss if left untreated. DME happens when small blood vessels are damaged in the retina (an area at the back of the eye where specialized cells sense light and send signals to the brain so that we can see). These damaged blood vessels become leaky and cause swelling (edema) in a central area of the retina called the macula . Current treatments for DME include medicines that reduce inflammation (called corticosteroids ) and medicines that block a protein called vascular endothelial growth factor ( VEGF ) that causes blood vessels to leak (these are called anti-VEGFs ). The purpose of the NEW DAY study was to compare the FAc implant (a corticosteroid ) with aflibercept (an anti-VEGF ) injections as a treatment for people with DME who had either minimal or no prior treatment. Worsening DME may occur in some people despite treatment. During the study, extra aflibercept injections were given when needed after the initial planned treatment. The study compared how many extra, or “rescue”, aflibercept injections were needed after the planned treatment. The study also compared the effect of each treatment on vision and swelling of the macula. Side effects of the treatments were also recorded. What were the results? After the planned treatments (either one FAc implant or five aflibercept injections), the average number of extra aflibercept injections was similar between groups. However, when counting the planned treatments, the total number of injections over 18 months was lower in people who received FAc. Rescue injections were needed sooner after the last scheduled aflibercept injection than after receiving a FAc implant. Regardless of initial treatment, improvements in vision and swelling of the retina were similar. Side effects, such as cataracts and increases in eye pressure, were more frequent with FAc than aflibercept. What do the results mean? Starting DME treatment with the FAc implant had similar benefits to vision and swelling as starting with aflibercept. People who started with FAc needed fewer total injections overall than those who started with aflibercept and had a longer time to requiring rescue injections. Side effects of FAc were as expected and were manageable. Knowing the timing of when they happened can help eye-care teams better monitor patients with DME and manage their care.